Video and the Analysis of Social Interaction. An interview with Christian Heath - Pentimalli, Barbara; Spreafico, Andrea (SocietàMutamentoPolitica, 2016)
Christian Heath is Professor at King’s College London and co-director of the Work, Interaction and Technology Research Centre. Drawing on Ethnomethodology and Conversation Analysis, he specialises in fine grained, video-based field studies of social interaction. He is currently undertaking research in settings that include auctions, control centres, operating theatres, and museums and galleries. His previous research involves a range of projects UK Research Councils and the European Commission in areas that include command and control, health care, the cultural industries, and advanced telecommunications. He has held positions at the Universities of Manchester, Surrey, and Nottingham and visiting positions at Universities and industrial research laboratories in the UK and abroad. He is an Fellow of the Academy of the Social Sciences (AcSS), a Freeman of the Worshipful Company of Art Scholars and in 2015 was given the EUSSET-IISI Lifetime Achievement Award presented to scholars for an outstanding contribution to the reorientation of the fields of computing and Informatics. His publications include: “The Dynamics of Auction: Social Interaction and the Sale of Fine Art and Antiques” (Cambridge 2013: awarded the Best Book Award in 2014 by the International Society for Conversation Analysis), “Video in Qualitative Research: Analysing Social Interaction in Everyday Life” (Sage with Hindmarsh, J. and P. Luff, 2010), “Technology in Action” (with P. Luff, Cambridge 2000), “Workplace Studies: Recovering Work Practice and Informing System Design” (Cambridge with Luff, P. and J. Hindmarsh 2000), “Body Movement and Speech in Medical Interaction” (Cambridge 1986) and numerous articles in journals and books. With Roy Pea and Lucy Suchman he is editor of the book series published by Cambridge University Press, Learning and Doing: Social, Cognitive and Computational Perspectives.